The Influence of Family Environment, ICT Literacy, Infrastructure on Learning Outcomes of Online Learning with Learning Motivation as Intervening Variables in State Vocational High Schools in Jepara Regency (Journal of Economic Education, 2022)
This study aims to examine the online learning outcomes of basic accounting subjects in State Vocational Schools throughout Jepara Regency which are influenced by family environment, ICT literacy, infrastructure with motivation as an intervening variable. The type of research used is quantitative research. Data were collected by questionnaire and analyzed using path analysis. The population in this study were all students majoring in accounting at State Vocational Schools throughout Jepara Regency which included SMK Negeri 3 Jepara, SMK Negeri 1 Batealit, SMK Negeri 1 Kedung, SMK Negeri 1 Bangsri. The total population in this study was 288 students, with a sample of 168 students. The results of this study indicate that this research model is good in measuring the research theme. (1)Family environment has a positive and significant effect on learning outcomes of 0.303, (2) ICT literacy has a positive and significant effect on learning outcomes of 0.187, (3) Infrastructure has a positive and significant effect on learning outcomes of 0.433, (4) Learning motivation has a positive and significant effect on learning outcomes. significant to the learning outcomes of 0.242. (5) Family environment has a positive and significant effect on learning outcomes through learning motivation of 0.05544, (6) ICT literacy has a positive and significant effect on learning outcomes through learning motivation of 0.110, (7) Infrastructure has a positive and significant effect on learning outcomes through learning motivation of 0.011.